RECEPTION ANALYSIS OF BROMANCE IN “RUN BTS!” VARIETY SHOW ON VLIVE VIDEO PLATFORM - Eka Perwitasari Fauzi; Rahmadya Putra Nugraha (IJRDO - Journal of Social Science and Humanities Research, 2020)
This study entitled reception analysis of bromance in “Run BTS!” variety show on vlive video platform. This study was a qualitative research with reception analysis method. The findings showed that the meaning was categorized in three positions of meaning i.e dominant, negotiation, and opposition. In this study, the meaning of bromance in general, nine out of eleven informants were in a dominant position. While in the position of negotiating, four informants interpreted that not all bromance interaction of Bangtan Sonyeondan (BTS) boy band members were pure and spontaneous, the four informans assessed there were some interactions that were parts of the program script to satisfy fans who mostly like bromance interactions that showed closeness among Bangtan Sonyeondan (BTS) members. In the position of opposition, five informants interpreted that the bromance interaction in the Bangtan Sonyeondan (BTS) boy band was very excessive and inappropriate for fellow men.